Effectiveness Of Waiting Area For Motorcyclists At Signalized Intersection - Abdrabou, Youssef Salaheldin Hegazy (Universiti Sains Malaysia, 2022)
The motorcycle is one of the most economical and viable options for affordable transport in most developing countries. Malaysia suffers from the onslaught of motorcycle crashes, contributing to more than 60 percent of road deaths yearly. While various countermeasures such as physical segregation of motorcyclists from other vehicles have been implemented, high conflict area such as the intersections remains an issue. The provision of a dedicated space for motorcyclists at intersections in the form of waiting area is not something new; providing targeted vehicles a head starts when the traffic signal changes from red to green. The City Council of Penang Island (MBPP) of the Penang state has recently adopted the use of waiting areas for the motorcyclist, this study was done to determine the significant motorcyclist’s behaviour in the waiting area at a signalized intersection, the effectiveness of the waiting area box for the motorcyclist, and the start-up lost time caused by the motorcyclist to the other road users. Data collection was conducted to collect the motorcyclist's behaviour in the waiting area, the utilization of the waiting area by the motorcyclist, and the additional time caused by the motorcyclist at a signalized intersection after the waiting area is in operation. The study found that the motorcyclist tends to enter the waiting area based on the results obtained from the extracted data. The effectiveness of the waiting area depends on the utilization of the waiting area and the occupancy rate used to determine the effectiveness. The southbound and the northbound approaches were chosen at the signalized intersection between Jalan Jelutong, and Jalan Sungai Pinang in Penang state based on the suitability of the location. the southbound and the northbound approaches positively affects the waiting area during morning and evening peak hours. Additionally, the southbound approach morning and evening occupancy rate is 77.22% and 55.56%, respectively, while the northbound approach for morning and evening peak hours is 50.00% and 50.83%, respectively. The occupancy rate shows that the effectiveness of the waiting area for both approaches at the signalized intersection between Jalan Jelutong and Jalan Sungai Pinang is above 50%, considered effective. However, the data obtained for the start-up lost time showed a significant increase in the additional time. For the southbound approach morning and evening, the delay time is 7.79 seconds and 7.30 seconds, respectively, while for the northbound approach, the delay time morning and evening are 7.53 seconds and 7.42 seconds, respectively.